Theophrastus of Eresus. sources for his life, writings, thought, and influence - Sharples, R. W. (Philosophia Antiqua, 1998)
This volume forms part of the large international Theophrastus project started by Brill in 1992 and edited by W.W. Fortenbaugh, R.W. Sharples and D. Gutas . Together with volumes comprising the texts and translations, the commentary volumes provide a new generation of classicists with an up-to-date collection of the fragments and testimonia relating to Theophrastus (c. 370-288/5 B.C), Aristotle's pupil and successor as head of the Lyceum. In the present volume, the focus is on natural philosophy, apart from the study of living things. Topics covered include the principles of scientific enquiry, place, time, motion, the heavens, the sublunary world, meteorology and the study of materials.